Análise econômico-financeira do mercado segurador brasileiro no período pós-plano Real - Santos, Ana Flavia Menezes (2016)
In order to identify indicators of economic and financial performance of insurance companies in the Brazilian market, a literature search on the subject in national and international literature was performed. horizontal and vertical analyzes were performed of Balance Sheets (BP) and the results of the exercises Statements (DRE) and the indicators constructed from the survey data on the basis of the Superintendency of Private Insurance (SUSEP) insurers. The study aims to identify and analyze the economic and financial performance of the Brazilian insurance market from 2000 to 2010. The verification of this analysis was performed using the data collected and worked all active insurance companies in Brazil in the period studied. From the data presented, the economic and financial ratios for the entire insurance market were calculated. The work presented a theoretical framework of the insurance, the Brazilian insurance market, its components and regulatory bodies, laws and specific industry standards, the design in the national context and the basic concepts and technical operations in the accounts of insurers. With the test results, we conclude that insurers achieved excellent financial performance in relation to the profitability ratios, the results were satisfactory.